A Comprehensive Review on Measurement and Correlation Development of Capillary Pressure for Two-Phase Modeling of Proton Exchange Membrane Fuel Cells - Chao Si; Xiao-Dong Wang; Wei-Mon Yan; Tian-Hu Wang (Journal of Chemistry)
Water transport and the corresponding water management strategy in proton exchange membrane (PEM) fuel cells are quite critical for the improvement of the cell performance. Accuracy modeling of water transport in porous electrodes strongly depends on the appropriate constitutive relationship for capillary pressure which is referred to as pc-s correlation, where pc is the capillary pressure and s is the fraction of saturation in the pores. In the present PEM fuel cell two-phase models, the Leverett-Udell pc-s correlation is widely utilized which is proposed based on fitting the experimental data for packed sands. However, the size and structure of pores for the commercial porous electrodes used in PEM fuel cells differ from those for the packed sands significantly. As a result, the Leverett-Udell correlation should be improper to characterize the two-phase transport in the porous electrodes. In the recent decade, many efforts were devoted to measuring the capillary pressure data and developing new pc-s correlations. The objective of this review is to review the most significant developments in recent years concerning the capillary pressure measurements and the developed pc-s correlations. It is expected that this review will be beneficial to develop the improved PEM fuel cell two-phase model.